Process of Identifying One's Life Calling At an Early Stage within the Youth Community of Gideon Cilegon Banten - Sirait, Rajiman Andrianus (PT. Riset Press International, 2023)
The identification of one's life purpose is a significant undertaking that contributes to the development of an individual's sense of self and life trajectory. Certain individuals possess the capacity to ascertain their life's purpose from their formative years, thereby affording them a distinct advantage in cultivating vocations that imbue their lives with significance and personal gratification. This article examines the significance and consequences of early identification of one's life purpose, with a specific emphasis on the various components that contribute to this process, as explored through collaboration with the Youth Gideon community. As part of conducting this study, a thorough examination of existing literature is undertaken to assess the findings of prior research and get a comprehensive comprehension of the subject matter. The findings of this research review indicate several elements that have led to the early identification of life calling. These aspects encompass familial influences, educational background, personal interests, and life experiences. Furthermore, this paper examines the ramifications of early identification of life purpose on personal growth and offers suggestions for educators, researchers, and professionals to facilitate the exploration and discovery of life calling among young individuals.